(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The evolution of ballet as an art form reflects the rich cultural and artistic heritage of societies worldwide. In Uzbekistan, ballet has undergone a remarkable journey, from its introduction during the Soviet era to its present status as a thriving component of the nation’s cultural identity. This article explores the historical development of ballet in Uzbekistan, highlighting key figures, institutions, and performances that have shaped its trajectory. Additionally, it examines the emergence of 3D ballet on the global stage, a revolutionary fusion of traditional choreography and advanced digital technology. By juxtaposing Uzbekistan’s ballet scene with the innovative trends in 3D ballet, this study underscores the transformative potential of integrating classical artistry with modern advancements, ultimately reshaping the future of this performing art.